Papulonecrotic Tuberculide: A Case Report (Journal of Medicine, 2014)
A 20 year old lady presented with asymptomatic papulo-pustular eruption over upper, lower extremities and the abdomen. There was no manifestation of tuberculosis elsewhere in the body. Investigations were suggestive of papulonecrotic tuberculide.DOI: http://dx.doi.org/10.3329/jom.v15i1.19876 J Medicine 2014; 15: 64-67